Again, Josefina! - Tripp, Valerie, 1951- (The American girls collection, 2000)
Nine-year-old Josefina wants to give up learning to play the piano until she sees how much joy her music gives to her baby nephew. Discusses the importance of music on the New Mexican frontier and describes how to dance La Vaquerita.